2013
DOI: 10.1007/s10734-013-9668-y
|View full text |Cite
|
Sign up to set email alerts
|

Academics job satisfaction and job stress across countries in the changing academic environments

Abstract: This study examined job satisfaction and job stress across 19 higher education systems. We classified the 19 countries according to their job satisfaction and job stress and applied regression analysis to test whether new public management has impacts on either or both job satisfaction and job stress. According to this study, strong market driven countries are in the high stress group and European countries are in the high satisfaction group. The classification implies that market oriented managerial reforms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
224
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(243 citation statements)
references
References 69 publications
(128 reference statements)
9
224
0
10
Order By: Relevance
“…Several reasons for the increased intensification of work in higher education (HE) could be identified stemming from the radical reforms experienced in the sector in many countries. These include the 'massification' of HE; a student body from an increasingly varied social, cultural and educational background; increased demands for transnational education; the introduction of market-led policies requiring diversification and regular redesign; more stringent requirements for accountability and efficiency; an increased pressure to publish; the introduction of more "judgemental" performance management systems regarding the direction, quality and impact of teaching and research output; and more rigorous monitoring of the student experience (Altbach, 2000;Bentley, Coates, Dobson, Goedegebuure, & Meek, 2013;Biron, Brun, & Ivers, 2008;Miller, Taylor, & Bedeian, 2011;Shin & Jung, 2014;Tytherleigh et al, 2005;Ter Bogt & Scapens, 2012;Winefield et al, 2008;Yussof & Khan, 2013). A shift towards a more bureaucratic and non-participative style of management has also been highlighted, which is widely considered incompatible with expectations of collegiality and academic freedom (Fanghanel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several reasons for the increased intensification of work in higher education (HE) could be identified stemming from the radical reforms experienced in the sector in many countries. These include the 'massification' of HE; a student body from an increasingly varied social, cultural and educational background; increased demands for transnational education; the introduction of market-led policies requiring diversification and regular redesign; more stringent requirements for accountability and efficiency; an increased pressure to publish; the introduction of more "judgemental" performance management systems regarding the direction, quality and impact of teaching and research output; and more rigorous monitoring of the student experience (Altbach, 2000;Bentley, Coates, Dobson, Goedegebuure, & Meek, 2013;Biron, Brun, & Ivers, 2008;Miller, Taylor, & Bedeian, 2011;Shin & Jung, 2014;Tytherleigh et al, 2005;Ter Bogt & Scapens, 2012;Winefield et al, 2008;Yussof & Khan, 2013). A shift towards a more bureaucratic and non-participative style of management has also been highlighted, which is widely considered incompatible with expectations of collegiality and academic freedom (Fanghanel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These studies focus, for instance, on measuring effects of NPM interventions on job satisfaction (Shin & Jung, 2014), on measuring performance reporting expectations (McDavid & Huse, 2012), seeking opinions about NPM-inspired interventions (Steyvers et al, 2010) or investigating the relationship between NPM-caused work alienation and organizational commitment (Tummers & Den Dulk, 2013).…”
Section: Journal Of Public Administration and Governancementioning
confidence: 99%
“…They were undertaken in various places (see for example, UK: Oshagbemi, 1996, Ward and Sloane 2000, Stevens 2005; Canada: Leckie and Brett 1997; Turkey: Kusku 2003, Bayram et al 2010, Toker 2011, Saygi et al 2011 Khalid et al 2012, Mehmood et al 2012, Sohail and Delin 2013, Syed and Ahmedani 2013; India. Shamra and Manani 2012; Jordan: Abushaira 2012; Vietnam: Wang et al 2014;Shin and Jung 2014 1 ). The following section will review in brief these studies.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
“…They also observed that the organization operates effectively only if teacher and staff can self-recognize themselves as important resources that have scarified all their life for the development of working place. Wang et al concluded In a comprehensive study of academicians' job satisfaction and job stress across 19 countries, Shin and Jung (2014) employed regression analysis to assess whether new public management affects job satisfaction or job stress. They noticed that while European countries are in the high satisfaction group, countries driven by strong market are in high stress group.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation